Konstruksi filosofis akad-akad ekonomi syariah - Ridwan Ridwan (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
The problem that frequently appears in Islamic economic contract is the debate on its normative legaland philosophical basis. This article will explain that many contracts in Islamic economic law are basedon the philosophy of law. The philosophy of Islamic economic law is based on triangle concept, i.e.philosophy of God, human being, and nature. It is characterized by God-oriented (rabbani) and humanity-oriented (insani) economy. Its God-oriented character preceives Allah (God) as the center ofhuman awareness in performing economic activities and it reflects in economic behavior considering thenature of human being and promoting the values of goodness, justice, and mutual relationship.